Preservation of the Muyu Indigenous Language with an Android-based Dictionary - Beatus Tambaip; Izak Habel Wayangkau; Suwarjono Suwarjono; Martha Loupatty; Aenal Fuad Adam; Hariyanto Hariyanto (Emerging Science Journal, 2020)
Indonesia is a country rich in cultural diversity, with each culture having its own regional language characterizing the area. The Muyu language is one of the regional languages, used by the Muyu tribal community in Boven Digoel Regency, Papua Province. The language is now under the threat of abandonment by the Muyu community, especially the younger generation. One of the causes is the lack of written learning media for the language to be inherited by older speakers in the form of books and electronic dictionaries. This study will try to develop an Android-based Muyu-Indonesian-English dictionary application using the waterfall method (classic life cycle). The aim is to test students' preferences and attitudes towards the development of Muyu language knowledge. The research sample consisted of 40 respondents consisting of Muyu students at Musamus University. A questionnaire was used to measure the extent of student responses to the use of the Muyu-Indonesian-English dictionary application. The test results show that the system has no errors in carrying out the functions that have been created previously at the manufacturing stage. The three-language Muyu-Indonesian-English dictionary application is able to search for vocabulary properly and correctly in Muyu, Indonesian, and English. The attitude of students towards the usefulness of this dictionary application is measured at the medium category, meaning that the application is useful as a tool to facilitate students of the Muyu language, especially Android users, in finding vocabulary in three languages, and can be a tool for learning the Muyu language and preserving local wisdom so that it does not become extinct. Doi: 10.28991/esj-2021-SP1-06 Full Text: PDF